Некоторые размышления о переводах «Бориса Годунова» на норвежский язык (Some Notes on Norwegian Translations of “Boris Godunov”) - Komarova, Olga (Poljarnyj vestnik, 1999)
The first translation (1974) was made into nynorsk by Olav Rytter, who has also translated several other works by Pushkin. The author of the other translation (1992), into bokmål, is Erik Bystad, a recognized literary critic and translator of Shakespeare. The specifically national features of the text present a lot of problems. In the Rytter translation one can trace an attempt to make the text easier to understand by leaving out some of the geographical and personal names. The Bystad translation is often closer to the original text, but less diverse in its rhythmic pattern. Both translations illustrate how difficult it is to find a satisfying solu- tion to the rhymed proverbs or plays on words. Russian standardized modes of address, mention of the tsars or certain historical events, Pushkin's choice of the name for the pretender-all this presents at times unresolvable problems for the translators. The analysis of the two translations not only lets us feel how important and responsible is the role of a translator in transnational cultural commu-nication, but also illustrates some techniques of this magnificent art.